Telephone-based cognitive screening tools: a scoping review - Ammawat, Watthanaree; Thavornpaiboonbud, Nonticha; Wangkawan, Thitiya; Attanak, Attapol; Oanmun, Keerathi = (Journal of Medicine and Health Sciences, 2022)
Abstract This scoping review of telephone-based cognitive screening or evaluation tools focuses on the review and analysis of cognitive components, the quality of tool assessment, and the application of the tools used for screening dementia among elderly people. This study searched for research on telephone-based cognitive screening or evaluation tools published between 2017 and 2021. All of the available studies were systematically analyzed and extracted for the assessment of cognitive components and filtered by the selection criteria. The results found that 12 studies with 14 tools met the eligibility criteria. The selected studies assessed the cognitive components from the highest to the lowest proportion, as follows: language (92.86%), orientation (78.57%) such as date, time, person, and place, and memory (50.00%), respectively. These studies met the psychological tool development and validation index; therefore, they could be used as a screening tool for elderly people with dementia. In conclusion, the selected studies, from foreign countries, these telephone-based cognitive screening tools covered the critical cognitive components, and met the social and cultural contexts. As a result, the development of a telephone-based cognitive screening tool in Thai version is essential.